Plant-Microbe Interactions in Alleviating Abiotic Stress—A Mini Review - Inbaraj, Michael Prabhu (Frontiers in Agronomy, 2021)
Crop plants are continuously exposed to various abiotic stresses like drought, salinity, ultraviolet radiation, low and high temperatures, flooding, metal toxicities, nutrient deficiencies which act as limiting factors that hampers plant growth and low agricultural productivity. Climate change and intensive agricultural practices has further aggravated the impact of abiotic stresses leading to a substantial crop loss worldwide. Crop plants have to get acclimatized to various environmental abiotic stress factors. Though genetic engineering is applied to improve plants tolerance to abiotic stresses, these are long-term strategies, and many countries have not accepted them worldwide. Therefore, use of microbes can be an economical and ecofriendly tool to avoid the shortcomings of other strategies. The microbial community in close proximity to the plant roots is so diverse in nature and can play an important role in mitigating the abiotic stresses. Plant-associated microorganisms, such as endophytes, arbuscular mycorrhizal fungi (AMF), and plant growth-promoting rhizobacteria (PGPR), are well-documented for their role in promoting crop productivity and providing stress tolerance. This mini review highlights and discusses the current knowledge on the role of various microbes and it's tolerance mechanisms which helps the crop plants to mitigate and tolerate varied abiotic stresses.